BEYOND RELIGIOUS VALIDITY: Evaluating Wali Muhakkam Through Legal Pluralism and Maqasid Al- Shari'ah in East Aceh - Said Rizal; Emir Syarif Fatahillah Pakpahan; Elvira Fitriyani Pakpahan; Heriyanti Heriyanti; Tommy Leonard (Al-Risalah, 2026)
Practices resembling wali muhakkam in unregistered marriages remain prevalent across various regions of Indonesia despite lacking formal recognition under national law. Existing scholarship has largely focused on the doctrinal validity of such marriages. At the same time, insufficient attention has been paid to the broader legal implications arising from competing normative authorities and their compatibility with the objectives of Islamic law. The study examines the practice of wali muhakkam in East Aceh through the combined lenses of legal pluralism and maqasid al shari'ah. Employing a social-legal approach, it integrates doctrinal analysis of Indonesian marriage law with empirical data obtained through interviews with religious leaders, imeu gampong, officials of the office of Religious Affairs, and couples involved in unregistered marriages. The findings reveal that wali mahakkam functions as an alternative source of normative authority situated between state law, religious norms, and social legitimacy. While the practice contributes to the realization of hifz al-din by facilitating marriages regarded as religiously valid. It does not consistently secure the broader objectives of maqasid al-shariah, particularly the protection of lineage (hifz al-nasl), property (hifz al-mal), and dignity (hifz al-ird). This study argues that religious legitimacy should not automatically be equated with substantive legal protection. It therefore proposes a maqasid-oriented reconstruction of guardianship regulation aimed at reconciling legal certainty, religious legitimacy, and social realities within Indonesia's plural legal order. The study further demonstrates that the persistence of wali muhakkam cannot be explained solely through legal pluralism but must also be evaluated according to its capacity to realize the substantive objectives of maqasid al-shari'ah.